Electroless Ni-Co-Cu-P Alloy Deposition In Alkaline Hypophosphite Based Bath - Zainal Abidin, Muhammad Zaimi; Azran, Mohd Nor; Muhamad, Khaizaki; M., Alifd; Abdul Aziz, Mohd Sanusi; Azam, Mohd Asyadi; Kasim, Mohd Shahir; Munawar, Rose Farahiyan; Abd Manaf, Mohd Edeerozey (Trans tech Publication, Switzerland, 2016)

(untitled)
The use of electroless deposition method to deposit nickel alloy attracts attention due to its uniformity, corrosion resistance in neutral media and low friction. Quaternary nickel alloy deposit can be achieved by adding metal ion additive into the plating bath.Furthermore,the use of alkaline bath can accelerate the deposition rate, and provide sufficient thickness for corrosion protection.In this study,an electroless quaternary nickel alloy is deposited on iron coupons by adding cobalt and copper ions in hypophosphite based Ni-P alkaline bath.The nickel alloy deposit surface morphology is studied using scanning electron microscope (SEM) and x-ray fluorescence (XRF).Corrosion behavior of the nickel alloy is investigated using polarization curve measurement in 3.5wt% NaCl aqueous solution.From the results,the elecroless Ni-Co-Cu-P alloy coating produced at higher plating bah pH is harder than the lower bath pH. Higher Co,Cu and P content in the Ni alloy exhibit broader passive area in the polarization curve measurement results.